Concept mapping for enhanced critical thinking in argumentative writing among ESL learners - Chan, Gwendolyn Hui Pei (2024)
Critical Thinking (CT) skills are indispensable in the 21st century. Writing, as one of the most difficult skills to master, becomes even more challenging when CT skills are demanded. Despite the encouragement of Higher Order Thinking Skills (HOTS) in the Malaysian English writing curriculum, writing skills among students are still below satisfactory levels as seen in Malaysian University English Test (MUET) reports. As Concept Maps (CM) are versatile and dynamic tools with a theoretical foundation in CT and Ausubel’s meaningful learning, the current study aims to investigate whether the incorporation of CM enhances CT in argumentative writing and determine the levels of CT in ESL learners’ argumentative writing. The study employed quantitative methods with an experimental design. 40 students from a secondary school in Perak, Malaysia were selected via purposive sampling. The Experimental Group (EG) underwent CM method in teaching argumentative writing whereas the Control Group (CG) underwent traditional methods to do so. Participants were administered essays for the pre- and post-tests which were then graded using the Illinois Critical Thinking Essay Rubric. The researcher employed Statistical Package for the Social Sciences (SPSS) and paired samples t-tests to analyse the pre-test and post-test scores of the different groups and the individual scores of the CT features in the rubric. It was found that the use of CM significantly contributed to enhancing the CT skills of the students in their argumentative writing, with the EG achieving a mean difference of 3.15 in their pre- and post-test scores, compared to the CG that achieved a mean difference of only 1.70. However, the participants CT levels were found to be far from ‘well-developed’ with an average score of only 3.9 out of 6 points, depicting the CT climate in Malaysian classrooms. This study holds implications as it highlights the importance of the integration of CM into ESL writing practices, the need for further CT instruction and the additional strategies that are needed for the CM approach to teach CT in Malaysian ESL classrooms.